Translation Theories in Computer Translation - Engliana Engliana (Journal of English Language and Culture, 2017)
There have been changes in recent years in the study of translation and languages due to advancement and development of technology including language processing for translation tools. Therefore, translation theories should raise an awareness of the needs for technology and software as parts of translators’ workbench. This paper provides insights into computer translation through the viewpoint of translation theory. It felt that the modern-day translators - professionals and amateurs as well as translator-researchers and language specialists – should be informed about this, aiming to increase awareness on the relationship between translation technology and translation theory. At the end, the journey arrives at the conclusion that both human translators and machine translation come upon problems during the process of translation. Keywords: translation theory, computer translation (CT), Transtool